KORYAKSKIY VOLCANO, KAMCHATKA: ERUPTION OF 1895-1896 WAS A MISINTERPRETATION - Melekestsev I.V. (My University, 1996)
The explosive-effusive eruption of 1895-1896 in Kamchatka, which has been attributed to Koryakskiy Volcano, did not occur and need be excluded from the list of Koryakskiy eruptions, as well as from the catalogs of regional and world eruptions of active volcanoes and other reference books.